2017
DOI: 10.1002/mnfr.201700601
|View full text |Cite
|
Sign up to set email alerts
|

Blueberry Metabolites Attenuate Lipotoxicity‐Induced Endothelial Dysfunction

Abstract: The presented findings indicate that the vascular benefits of blueberry anthocyanins are mediated by their metabolites. Blueberries might complement existing therapies to lessen vascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 48 publications
2
50
1
Order By: Relevance
“…Wild blueberry consumption is associated with glucose metabolism in metabolic syndrome obese rats [ 82 ]. The metabolism of blueberry anthocyanins lightens the endothelial dysfunction of lipid toxicity and lessens vascular complications associated with diabetes [ 55 ] (see Table 1 ). Blueberry can lighten vascular complications in diabetes as some of its metabolites can restore cell surface glycosaminoglycans and attenuate endothelial inflammation [ 83 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…Wild blueberry consumption is associated with glucose metabolism in metabolic syndrome obese rats [ 82 ]. The metabolism of blueberry anthocyanins lightens the endothelial dysfunction of lipid toxicity and lessens vascular complications associated with diabetes [ 55 ] (see Table 1 ). Blueberry can lighten vascular complications in diabetes as some of its metabolites can restore cell surface glycosaminoglycans and attenuate endothelial inflammation [ 83 ].…”
Section: Preventive Chronic Disease Of Blueberrymentioning
confidence: 99%
“…C3G possesses strong antioxidant activity potentially due to the two hydroxyls on the B ring [6], as shown in Figure 1. Recent studies have suggested that C3G potentially exerts functions primarily through C3G metabolites (C3G-Ms) [7], and more than 20 kinds of C3G-Ms have been identified in serum by a pharmacokinetics study in humans [8]. Although the function and mechanism of C3G-Ms are still not clear, protocatechuic acid (PCA) [9][10][11][12], phloroglucinaldehyde (PGA) [1], vanillic acid (VA) [13][14][15], ferulic acid (FA) [16][17][18][19], and their derivates represent the main bioactive metabolites of C3G due to their antioxidant and anti-inflammatory properties.…”
Section: Introductionmentioning
confidence: 99%
“…After careful application of the inclusion and exclusion criteria to the citations collected with the databases search, the numbers of human studies selected for this review were 22 studies out of 206 for blueberry intake [ 2 , 3 , 12 , 13 , 32 , 34 , 37 , 50 , 81 83 , 91 , 103 , 105 , 106 , 112 , 137 , 153 , 160 , 178 , 185 ]; 20 out of 137 for strawberries [ 4 , 5 , 9 , 14 , 20 , 22 , 26 , 31 , 41 , 48 , 74 , 75 , 113 , 126 , 129 , 141 , 147 , 148 , 165 , 179 ], 7 out of 87 for raspberry [ 70 , 78 , 86 , 95 , 98 , 156 , 184 ], 5 out of 66 for blackberries [ 47 , 64 , 89 , 100 , 161 ], 13 out of 236 for cranberries [ 7 , 27 , 49 , 51 , 94 , 108 , 119 , 127 , 135 , 174 176 , 183 ], and 8 out of 61 for blackcurrant […”
Section: Resultsmentioning
confidence: 99%